Online Single Submission (OSS) Izin Usaha pada DPMPTSP Kabupaten Nagan Raya - Sundari, Desi Wiwi (Regress: Journal of Economics & Management, 2022)
This article aims to discuss the Online Single Submission (OSS) for Business Permits at DPMPTSP Nagan Raya Regency. The research was conducted in Nagan Raya to see how acceptable Online Single Submission (OSS) as a solution for obtaining business permits was accepted by service users. OSS is then analyzed using the Technology Acceptance Model/TAM to see which constructs are most influential in the process of accepting this technology to replace conventional service processes. A total of 73 research respondents were involved in this study taken from entrepreneurs who use business license processing services at DPMPTSP Nagan Raya. All constructs of research variables were tested using the Partial Least Square (PLS) method and the results obtained showed that behavior intention occupies a position as the dominant construct affecting technology acceptance behavior.